2017
DOI: 10.1111/1471-0528.14822
|View full text |Cite
|
Sign up to set email alerts
|

The effect of laparoscopic resection of large niches in the uterine caesarean scar on symptoms, ultrasound findings and quality of life: a prospective cohort study

Abstract: ObjectiveTo evaluate the effectiveness of a laparoscopic niche resection on niche‐related symptoms and/or fertility‐related problems, ultrasound findings and quality of life.DesignProspective cohort study.SettingUniversity hospital.PopulationWomen with a large niche (residual myometrium <3 mm) and complaints of either postmenstrual spotting, dysmenorrhoea, intrauterine fluid accumulation and/or difficulties with embryo transfer due to distorted anatomy.MethodsWomen filled out questionnaires and a validated men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
94
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(99 citation statements)
references
References 32 publications
4
94
1
Order By: Relevance
“…Significant improvements were reported in number of days of postmenstrual spotting (4 versus 7 days; P = 0.04) and in postmenstrual spotting‐associated pain ( P = 0.02) . In a similar interventional study of symptomatic women undergoing laparoscopic niche resection of large caesarean niches, defined as RMT <3 mm, repair resulted in an almost 80% improvement in the symptoms of postmenstrual spotting, dysmenorrhoea and pelvic pain …”
Section: Management Of Caesarean Niche‐related Symptomsmentioning
confidence: 95%
See 2 more Smart Citations
“…Significant improvements were reported in number of days of postmenstrual spotting (4 versus 7 days; P = 0.04) and in postmenstrual spotting‐associated pain ( P = 0.02) . In a similar interventional study of symptomatic women undergoing laparoscopic niche resection of large caesarean niches, defined as RMT <3 mm, repair resulted in an almost 80% improvement in the symptoms of postmenstrual spotting, dysmenorrhoea and pelvic pain …”
Section: Management Of Caesarean Niche‐related Symptomsmentioning
confidence: 95%
“…Different terms have since been used to describe the same phenomenon, including caesarean scar defect, isthmocele, post‐caesarean section scar defect (PCSD), caesarean niche, and caesarean delivery scar pouch . Caesarean niche is commonly identified on ultrasound as a hypoechoic area seen in the anterior lower segment, representing a defect in the myometrium as a result of poor healing of the uterine scar created at hysterotomy.…”
Section: Caesarean Scar Defect and Disordered Uterine Wound Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…35,45,51,64,[68][69][70][71][72][73][74][75][76][77][78][79] Laparoscopy is a technique that has to be preferred especially if the residual myometrial thickness is < 3 mm. 78 A skilled laparoscopic surgeon can use conventional laparoscopy or robotic-assisted surgery to correct the isthmocele. 25 After the defect is identified, it is cut open and the isthmocele and the surrounding fibrotic tissue are trimmed carefully and removed from the edges of the defect to access the healthy myometrium.…”
Section: Laparoscopymentioning
confidence: 99%
“…In fact, Api et al 79 analyzed the myometrial thickness, finding a mean value of 2 mm (0.7-6.2 mm) before the laparoscopy and of 9.8 mm (2.5-13.1 mm) after the surgery. Vervoort et al 78 published the first large prospective cohort study that evaluated the effect of laparoscopic isthmocele resection on symptoms, on fertility, and on ultrasound findings, evaluating 101 women. In this study, Vervoort et al 78 showed that the laparoscopic approach reduces postmenstrual spotting and its correlated discomfort, reduces dysmenorrhea, and enlarges the residual myometrial thickness 6 months after the intervention.…”
Section: Laparoscopymentioning
confidence: 99%